Marketing : the retro revolution - Brown, Stephen, 1955 March 23- (SAGE, 2001)
Retro-marketing is all around us, whether it be retro-products like the neo-Beetle, retro-scapes, such as Niketown, or retro-advertising campaigns, which make the most of the advertiser's glorious heritage. The rise of retro has led many to conclude that it represents the end of marketing, that it is indicative of inertia, ossification and the waning of creativity. Marketing - The Retro Revolution explains why the opposite is the case, demonstrating that retro-orientation is a harbinger of change and a revolution in marketing thinking. In his engaging and lively style, Stephen Brown shows that.